Wykonywanie środków o charakterze wolnościowym w prawie karnym skarbowym - Sawicki, Janusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The article concerns selected problems relating to libertarian measures in fiscal penal law from the perspective of criminal law enforcement. The issues addressed in the article first present the model of criminal policy in fiscal penal law. Then, the author analyses the institutions described in the Fiscal Penal Code, having the character of libertarian measures. All these measures relate to the imprisonment for fiscal offences. The article ends with a summary of libertarian measures in fiscal penal law.
Keywords: prawo karne skarbowe; model polityki kryminalnej; środki libertariańskie